Tolerance Values Representation in Indonesia Electronic EFL Textbook - Nuryansyah Adijaya (IKIP PGRI Pontianak, 2020)
Teaching students tolerance values play an important role to give them knowledge about how to live together in harmony, respect others, avoid potential conflicts and so on. This study is aimed at analyzing tolerance values representation in the 1st grade of Junior High School EFL Textbook published by Indonesian Ministry for Education and Culture (Kemendikbud). There are 4 kinds of tolerance values were analyzed; peace maker, cultural diversity, democracy and religious values. Qualitative content analysis was used to analyze tolerance values representation in the texts, illustrations, instructions, and exercises of the textbooks. The research shows that the textbook covers 72 tolerance values; 24 peace maker, 19 cultural diversity, 15 democracy, and 14 religious values. However, the textbook needs deeper exploration about the values to help students get vivid points of view about tolerance by giving them more real-life samples, and discussions.